1978
DOI: 10.1113/jphysiol.1978.sp012235
|View full text |Cite
|
Sign up to set email alerts
|

Plasma adrenaline, noradrenaline and dopamine in man and different animal species

Abstract: SUMMARY1. The catecholamines adrenaline (A), noradrenaline (NA) and dopamine (DA) were determined in plasma samples of man and various animal species using a highly sensitive radioenzymatic method.2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
71
2
2

Year Published

1979
1979
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(90 citation statements)
references
References 20 publications
12
71
2
2
Order By: Relevance
“…As found by Morgan et al (1985), the increase in sensitivity is such that the concentrations of hormones that are inducing the effects on Ca2l fluxes is well within the physiological range. Buhler et al (1978), for example, have analysed the circulating glucagon and noradrenaline concentrations, finding these to be 0.1-0.01 nM. Conditions of severe stress, like some other conditions in vivo, cause a concomitant increase in plasma adrenaline and glucagon (Eigler et al, 1979).…”
Section: Other Ca2+ Flux-related Signals Generated By Glucagonmentioning
confidence: 99%
“…As found by Morgan et al (1985), the increase in sensitivity is such that the concentrations of hormones that are inducing the effects on Ca2l fluxes is well within the physiological range. Buhler et al (1978), for example, have analysed the circulating glucagon and noradrenaline concentrations, finding these to be 0.1-0.01 nM. Conditions of severe stress, like some other conditions in vivo, cause a concomitant increase in plasma adrenaline and glucagon (Eigler et al, 1979).…”
Section: Other Ca2+ Flux-related Signals Generated By Glucagonmentioning
confidence: 99%
“…However, this response is lost after 2 wk of age. Although substantially lower than levels reached during labor, resting postnatal epinephrine levels (19) are above the threshold for absorption in the fetus, and it was naturally assumed (18) that this mechanism was sufficient to account for the postnatal absorptive phenotype. However, more recent work (63) does not support this hypothesis.…”
Section: Role Of the 〉-Adrenoceptor-dependent Pathway In Postnatal Lungmentioning
confidence: 99%
“…Plasma NE levels in man increase with age (Ziegler et al, 1976;Sever et al, 1977). Resting values, recently determined in carefully carried out studies, are reported to vary between 10" 10 and 2 X 10~9 M (De Champlain et al, 1976;Buhler et al, 1978).…”
Section: Sensitivity Of A-and ^-Adrenergic Receptormediated Responsesmentioning
confidence: 99%